Acute Thermotherapy Prevents Impairments in Cutaneous Microvascular Function Induced by a High Fat Meal - Jennifer C. Harvey; Bruno T. Roseguini; Benjamin M. Goerger; Elizabeth A. Fallon; Brett J. Wong (Journal of Diabetes Research)
We tested the hypothesis that a high fat meal (HFM) would impair cutaneous vasodilation, while thermotherapy (TT) would reverse the detrimental effects. Eight participants were instrumented with skin heaters and laser-Doppler (LD) probes and tested in three trials: control, HFM, and HFM + TT. Participants wore a water-perfused suit perfused with 33°C (control and HFM) or 50°C (HFM + TT) water. Participants consumed 1 g fat/kg body weight. Blood samples were taken at baseline and two hours post-HFM. Blood pressure was measured every 5–10 minutes. Microvascular function was assessed via skin local heating from 33°C to 39°C two hours after HFM. Cutaneous vascular conductance (CVC) was calculated and normalized to maximal vasodilation (%CVCmax). HFM had no effect on initial peak (48 ± 4 %CVCmax) compared to control (49 ± 4 %CVCmax) but attenuated the plateau (51 ± 4 %CVCmax) compared to control (63 ± 4 %CVCmax, P < 0.001). Initial peak was augmented in HFM + TT (66 ± 4 %CVCmax) compared to control and HFM (P < 0.05), while plateau (73 ± 3 % CVCmax) was augmented only compared to the HFM trial (P < 0.001). These data suggest that HFM negatively affects cutaneous vasodilation but can be minimized by TT.